Realization of smart home key management mechanism based on ECC - Wenbin CHENG; Jia LIU (Dianxin kexue)
At present,the data encryption technology of smart home system uses symmetric encryption method,but there is a problem with key management in this way.To achieve the security of the key,the smart home system uses asymmetric encryption technology.On this basis,the key management mechanism based on ECC was designed to achieve the purpose of guaranteeing key security.The key management mechanism includes an ECC-based data encryption key management mechanism and an ECC-based digital signature key management mechanism.So that the wireless network node in the identity authentication,the key generation,distribution,storage,update and other aspects of the key security were guaranteed.Finally,the security,time-consuming and scalability of this mechanism were analyzed.The results show that the mechanism has strong security and expansibility,and it is superior to E-G key management scheme in time-consuming.